Resposta hidrológica em cursos efêmeros no semiárido em função da cobertura vegetal e do padrão de chuva - Rodrigues, Rafael do Nascimento (2016)
The knowledge the factors involved in the hydrological response of a watershed is essential to the planning and management of water resources. The aim of this study was to answer the question of how the vegetation of tropical dry forest and the rainfall patterns can influence on the coefficient of runoff generated by rainfall different heights. Data were related to the rainy seasons of the years 2008 to 2013. We monitored the runoff two watersheds: scrub in regeneration for 35 years (CReg35) and thinned caatinga (CRal). At baseline, 2008, both watersheds had the same vegetation cover (CReg35), only at the end of this year was made the sleaze of the watersheds, eliminating the trees with a diameter less than 10 cm. precipitation events were classified in the standards: advanced, intermediate and late rains. To identify whether the flow coefficients generated before and after the thinning vegetation presented significant differences, applied to the test "t" Studart the level of 1%. Before thinning (2008), the class of P ≤ 30 mm recorded the highest percentage of runoff coefficient were significantly different at the 1% level of significance for other years. large magnitude events (> 50 mm) the flow is more dependent on rain characteristics and soil moisture conditions. The thinning caused a reduction in total annual runoff monitored during the five years (2009-2013) the P ≤ 30 mm, with a 46.2% difference in flow CRal in relation to the effective precipitation CReg35. Further development of the herbaceous layer due to thinning resulted in impediment to the runoff flow, requiring larger blade hasty to generate flow. The average flow rate was 10.43% for the watershed with CReg35 and 6.01% for the CRal. The response of the flow before the rainfall patterns followed the same trend in both watersheds, with higher effective rainfall recorded for intermediate patterns followed by the delayed and advanced. The existing herbaceous in CRal reduced surface flow, which resulted in a lower effective precipitation in different patterns of rainfall compared to CReg35. 50 mm) the flow is more dependent on rain characteristics and soil moisture conditions. The thinning caused a reduction in total annual runoff monitored during the five years (2009-2013) the P ≤ 30 mm, with a 46.2% difference in flow CRal in relation to the effective precipitation CReg35. Further development of the herbaceous layer due to thinning resulted in impediment to the runoff flow, requiring larger blade hasty to generate flow. The average flow rate was 10.43% for the watershed with CReg35 and 6.01% for the CRal. The response of the flow before the rainfall patterns followed the same trend in both watersheds, with higher effective rainfall recorded for intermediate patterns followed by the delayed and advanced. The existing herbaceous in CRal reduced surface flow, which resulted in a lower effective precipitation in different patterns of rainfall compared to CReg35."